Application of phytobiotics and straw fermentation for sheep feed in Mulawari Village, Karo Regency - patriani, peni patriani (Journal of Saintech Transfer, 2025)
The "Subur Tani" Farmer Group in Mulawari Village, Karo Regency, North Sumatra, faces significant challenges, including limited scientific and technological knowledge, environmental pollution from burning agricultural waste, and suboptimal livestock productivity exacerbated by disease threats. These issues directly hinder farmer profitability and highlight a critical need for improved skills in disease prevention. This community service program primarily aimed to enhance farmer capabilities in sustainable livestock management. The community service team delivered practical training on producing multifunctional phytobiotics and implementing fermented feed technology using agricultural waste. Key achievements include significant skill improvement among participating farmers: 86.7% became proficient in phytobiotic production, and 93.3% became skilled in fermented feed preparation. The program successfully demonstrated that applying these innovations enhanced livestock productivity, increased farmer income by reducing feed and medicine costs, and notably improved overall farmer skills. In conclusion, integrating phytobiotics and fermented feed offers a viable and impactful strategy for boosting livestock productivity, profitability, and skill development within agricultural communities like Mulawari Village.